A posthumanist reading of the “happy” fish in The Zhuangzi - Wang, Quan (Asian philosophy, 2024)
This article argues for an alternative interpretation of the happy fish scene in The Zhuangzi: the fish are not happy. The fish undergo an unpleasant experience while the philosophers debate animatedly over the joy of the fish. The dramatization of the fish scene compels us to contemplate anthropocentrism and species communication. Moreover, the contrast between the fish-bird becoming and the subsequent human narrations reinforces the anthropocentric usurpation of nonhuman agency. To get away from anthropocentrism, Zhuangzi proposes a posthumanist approach to deal with species communication in three interconnected stages: to acknowledge the limits of human cognition, to forget anthropocentric prejudice, and to de-obscure childlike innocence.